Displaced human skeletal remains in predynastic period - Marei, Sarah (AUC Knowledge Fountain, 2016)
Numerous burials dating to the Predynastic Period have been documented as containing bodies that appear to have been deliberately manipulated in a variety of ways. Among the practices noted is a deliberate rearrangement of skeletons. To date, these burials have received little scholarly attention and are most frequently attributed to looting or post-depositional disturbance, despite the evidence potentially pointing to an ancient and discontinued funerary ritual. Recent discoveries made in Predynastic cemeteries have revealed additional cases that reaffirm the presence of peculiar funerary practices taking place during that period. This thesis examines burials from the Predynastic cemeteries of Naqada, Gerza, Adaima and Tell El Farkha, presenting and analyzing evidence for deliberately displaced skeletal remains, in order to establish underlying patterns and to understand their significance. The burials are investigated through an interpretative approach, placing them within their historical, social and religious contexts. The evidence offers the possibility of elucidating a complex and dynamic mortuary culture that was practiced in the Predynastic Period.